Pengaruh Total Asset Turnover, Current Ratio dan Debt to Equity Ratio terhadap Return On Equity pada Perusahaan Kesehatan yang Terdaftar di BEI Tahun 2022-2024 - Dwi Aulia; Nisfu Fhitri (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the effect of Total Asset Turnover (TATO), Current Ratio (CR), and Debt to Equity Ratio (DER) on Return on Equity (ROE) in healthcare sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The healthcare industry experienced significant growth in recent years; however, fluctuations in profitability indicate that financial performance has not always aligned with theoretical expectations. This condition encourages further investigation regarding the influence of asset efficiency, liquidity, and capital structure on company profitability. The research applied a quantitative descriptive approach using secondary data obtained from annual financial reports. The sample was selected through purposive sampling and consisted of 12 healthcare companies with 36 observations. Data analysis was conducted using multiple linear regression supported by SPSS software and classical assumption tests. The findings indicate that TATO, CR, and DER simultaneously have a significant effect on ROE. Partially, TATO and CR show a positive and significant influence on ROE, indicating that efficient asset utilization and strong liquidity contribute to improving shareholder returns. In contrast, DER does not significantly affect ROE, suggesting that the use of debt has not been optimized to enhance profitability in healthcare companies during the observation period.